Wearable medical devices in health care system - Pentapati, Ramani (International Journal of Indigenous Herbs and Drugs, 2025)
The review emphasizes the growing significance of wearable technology in personalized healthcare, showcasing its ability to customize treatments by leveraging individual health data and predictive analytics to prevent diseases. Different types of wearable devices, such as skin-based, textile-based, and biofluidic-based wearables, play a crucial role in monitoring and managing a range of medical conditions, including cardiovascular diseases, hypertension, neurocognitive disorders, and muscle disorders. These technologies provide real-time, continuous monitoring of key health indicators, empowering both patients and healthcare providers to detect abnormalities early and intervene before conditions worsen. In addition to monitoring, wearable devices are evolving as platforms for drug delivery, further broadening their applications in the healthcare sector. This advancement positions wearables not only as tools for tracking health metrics but also as active participants in treatment, enabling timely therapeutic interventions. The widespread adoption of wearable technologies, including fitness trackers and biosensors, has fundamentally transformed traditional health monitoring systems by offering users the ability to continuously track vital signs such as heart rate, blood pressure, and blood glucose levels. This continuous monitoring facilitates a shift from a reactive to a proactive healthcare approach, where prevention and early intervention become key priorities. As technology continues to advance, wearable devices are expected to play an even more prominent role in personalizing healthcare, improving patient outcomes, and promoting a healthier population through early disease detection and management.